2002
DOI: 10.1095/biolreprod66.2.415
|View full text |Cite
|
Sign up to set email alerts
|

Long-Day Inhibition of Reproduction and Circadian Photogonadosensitivity in Zembra Island Wild Rabbits (Oryctolagus cuniculus)

Abstract: We investigated the effects of photoperiod on testicular activity in wild rabbits (Oryctolagus cuniculus) captured on Zembra Island (North Tunisia) and maintained in experimental photoperiodic conditions. Sexually inactive animals were subjected to alternate 3-mo periods of short days (8L:16D) and long days (16L:8D) for 1 yr. Testicular activity increased significantly and then decreased to levels equivalent to or lower than those measured during sexual quiescence after 1 mo of 8L:16D or 16L:8D, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Previous work on young male F344 and BN rats indicated that reproductive and body masses were reduced by SP (Heideman and Sylvester, 1997;Lorincz et al, 2001). SP has also been observed to have an inducing effect on male reproductive parameters in Zembra Island wild rabbits (Oryctolagus cuniculus) (Ben Saad and Maurel, 2002).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous work on young male F344 and BN rats indicated that reproductive and body masses were reduced by SP (Heideman and Sylvester, 1997;Lorincz et al, 2001). SP has also been observed to have an inducing effect on male reproductive parameters in Zembra Island wild rabbits (Oryctolagus cuniculus) (Ben Saad and Maurel, 2002).…”
Section: Discussionmentioning
confidence: 96%
“…Depending on the species, photoperiod may either trigger onset of the reproductive period (a stimulating effect), or initiate gonadal regression (an inhibitory effect). In long-day breeding species, the seasonal increase ij sexual activity occurs when the amount of daylight increases, and in short-day breeding species, the reproductive season is triggered by the shortening of day length, (Ben Saad and Maurel, 2002). Melatonin, a 5-methoxyindole synthesized by the pineal gland, plays a major role in photoperiod-mediated control of reproduction in mammals with seasonal breeding patterns determined by day length in their natural environment, and the circadian pattern of melatonin secretion constitute an endocrine message that provides information regarding the photoperiod (Reiter, 1986;Reiter, 1991;Arendt, 1995;1995;Goldman, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Also, Olayaki et al (2008) showed that there was significant reduction in reproductive organ mass, viability, counts, and sperm motility when rats were exposed to short photoperiod. On the other hand, Ben Saad and Maurel (2002) reported that short photoperiod has an improvement effect on male reproductive characteristics in wild rabbits. Moreover, long photoperiod resulted in non-significant increase in sperm properties, but it increased the testis weight (Olayaki et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These reproductive differences between domestic and wild rabbit depend on some candidate genes that regulate clock functions and reproduction [ 74 ]. Reproductive activity is mainly determined by factors that mainly affect males, such as their photoperiod (some studies have indicated that testicular activity and growth are affected by circadian cycles [ 75 , 76 ]), and others that affect both females and males, such as social interactions and climatology [ 77 ]. However, the most relevant factor related to reproduction seasonality seems to be nutrition.…”
Section: Reproduction In Rabbitsmentioning
confidence: 99%